2018 17th ACM/IEEE International Conference on Information Processing in Sensor Networks (IPSN) 2018
DOI: 10.1109/ipsn.2018.00055
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond-Precision Time-of-Arrival Estimation for Aircraft Signals with Low-Cost SDR Receivers

Abstract: Precise Time-of-Arrival (TOA) estimations of aircraft and drone signals are important for a wide set of applications including aircraft/drone tracking, air traffic data verification, or self-localization. Our focus in this work is on TOA estimation methods that can run on low-cost software-defined radio (SDR) receivers, as widely deployed in Mode S / ADS-B crowdsourced sensor networks such as the OpenSky Network. We evaluate experimentally classical TOA estimation methods which are based on a cross-correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Table 1.1 shows the software released as open source along this thesis. [4,7] LTESS-Track GPLv3 github.com/electrosense/LTESS-track [3] dump1090-hp GPLv3 github.com/openskynetwork/dump1090-hptoa [5] Mode S decoder GPLv3 github.com/openskynetwork/modes-uplink-decoder [6]…”
Section: Software Released As Open Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…Table 1.1 shows the software released as open source along this thesis. [4,7] LTESS-Track GPLv3 github.com/electrosense/LTESS-track [3] dump1090-hp GPLv3 github.com/openskynetwork/dump1090-hptoa [5] Mode S decoder GPLv3 github.com/openskynetwork/modes-uplink-decoder [6]…”
Section: Software Released As Open Sourcementioning
confidence: 99%
“…We have developed a web front-end to enable easy visualization of the spectrum data 5 . The spectrum visualizer allows interactive sensor selection and varying frequency resolution for detailed spectrum viewing.…”
Section: Live and Historical Spectrum Visualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…At the data-link level, the ADS-B message is encapsulated in Mode-S frames. As such, ADS-B uses Pulse-Position Modulation (PPM) and the replies/broadcasts are encoded by a certain number of pulses, each pulse being 1 µs long [14].…”
Section: Ads-b In a Nutshellmentioning
confidence: 99%
“…More recent works also demonstrate that is possible to apply the MLAT algorithm for detecting malicious ADS-B transmitters [ 30 , 31 ]; they also propose to improve the MLAT performance by optimizing the network geometry (using genetic algorithms) and smoothing the measurements by the use of Kalman filters. Finally, in [ 32 ], it was shown that it is possible to achieve precise TDOA estimation also using low-cost ADS-B receivers in the MLAT sensor network.…”
Section: Introductionmentioning
confidence: 99%